Weaknesses in primary health care favor the growth of acquired syphilis. - Marquiony Marques Dos Santos; Tatyana Maria Silva de Souza Rosendo; Ana Karla Bezerra Lopes; Angelo Giuseppe Roncalli; Kenio Costa de Lima (Public Library of Science (PLoS), 2021)
Acquired syphilis is a sexually transmitted infection that affects the general population and has been growing in recent years in many countries. A study was developed aiming to analyze the trends of acquired syphilis associated with sociodemographic aspects and primary health care in Brazil, in the period from 2011 to 2019. This study used secondary data from the national notification systems of the 5570 Brazilian cities and a database of 37,350 primary health care teams, as well as socioeconomic and municipal demographic indicators. The trends of acquired syphilis at the municipal level were calculated from the log-linear regression, crossing them with variables of primary health care and sociodemographic indicators. Finally, a multiple model was built from logistic regression. 724,310 cases of acquired syphilis have been reported. In primary care units, 47.8% had partial coverage and 74.1% had health teams with poor or regular scores. 52.6% had rapid test for syphilis partially available. Male and female condoms are available in 85.9% and 62.9% respectively and 54.4% had penicillin available in the health facility. The increase in trends of acquired syphilis was associated with better availability of the rapid test; lower availability of male condoms; lower availability of female condoms; lower availability of benzathine penicillin; partial coverage of the teams in primary health care; limited application of penicillin in primary health care; higher proportion of teams classified as Poor/Regular in primary health care; higher proportion of women aged 10 to 17 years who had children; higher HDI; higher proportion of people aged 15 to 24 years who do not study, do not work and are vulnerable; and population size with more than 100,000 inhabitants. The following variables remained in the multiple model: not all primary health care teams apply penicillin; higher proportion of primary health care teams with poor/regular scores; population size >100000 inhabitants; partially available female condom. Thus, the weakness of primary health care linked to population size may have favored the growth of the acquired syphilis epidemic in Brazilian cities.